(untitled) (Bangladesh Journal of Pharmacology, 2013)
This study investigated the antidiabetic and hypolipedemic action of Meyna spinosa leaf fractions. Effect of methanol, ethyl acetate and petroleum ether fraction (75 and 150 mg/kg p.o.) from M. spinosa leaf methanol extract was evaluated in high fat diet-alloxan induced type 2 diabetic rats after 21 days treatment. Glibenclimide (5 mg/kg), methanol and ethyl acetate fraction at 150 mg/kg exhibited 57.7, 63.4 and 53.8% reduction in serum glucose level after 21 days. Fractions demonstrated significant decrease in triglycerides, total cholesterol, low density lipid, very low density lipid, ?-amylase level, and increase in body weight, high density lipid level in diabetic rats. Fractions showed significant (p<0.05) hypoglycemic effect in glucose loaded animals but not in normal rats. Petroleum ether fraction did not produced significant effect. Result validated the claim made by folk medicinal uses and confirmed the antidiabetic potential of methanol and ethyl acetate fraction of M. spinosa.